Effect of Gestational Diabetes on Purkinje and Granule Cells Distribution of the Rat Cerebellum in 21 and 28 days of Postnatal Life - Elahe Mirarab Razi; Soraya Ghafari; Mohammad Jafar Golalipour (Basic and Clinical Neuroscience, 2015)
Introduction: Diabetes mellitus is associated with nervous system alterations in both human and animal models. This study was done to determine the effect of gestational diabetes on the Purkinje and granular cells in the cerebellum of rat offspring.